Assessing orbital vs. volcanic control on carbon cycle during the Early Cretaceous - Martinez, M. (2021)
The interval from the Valanginian to the Barremian stages (137?121 Ma; Early Cretaceous) ispunctuated by several episodes of environmental changes, accompanied by shifts in weatheringintensity on the continents and changes in the Tethyan neritic carbonate production. Wesynthetize here the astrochronology of two recent studies performed in the Neuquén basin,Vocontian Basin and Subbetic Domain (Aguirre-Urreta et al., 2019; Martinez et al., 2020), anchoredto CA-ID-TIMS U-Pb ages, which conclusions have been included in the Geologic Time Scale 2020(Gale et al, in press). We applied this time scale to a compilation of carbon-isotope ratio frombelemnites and proxies of detrital supply in the Tethyan area (Vocontian Basin and SubbeticDomain). From this compilation, we show that the episodes of environmental changes are pacedby a 2.4-Myr cycle and, with a lower amplitude, a 1.2-Myr cycle. In addition, the new time scaleshows the synchronicity between the Weissert Event and the Parana-Etendeka Large IgneousProvince. In the series of carbon-isotope ratios measured on belemnite rostra, the amplitude ofthe 2.4-Myr cycle is twice higher during the Valanginian than in the Late Barremian and threetimes higher than in the Hauterivian and Early Barremian, suggesting that the activity of theParana-Etendeka Large Igneous Province amplified the initial orbital forcing to trigger theenvironmental changes observed during the Mid-Valanginian.